Objectively assessed physical activity and weight status of primary school children in Germany with and without migration backgrounds. (August 2019) - Kobel, S.; Kettner, S.; Hermeling, L.; Dreyhaupt, J.; Steinacker, J.M.
Abstract: Objectives: Many children are insufficiently active, and children with a migration background appear to be even less active and at a higher risk of developing obesity. This study evaluated the weight status, and the frequencies and intensities of objectively assessed physical activity (PA) of children with and without a migration background. Study design: Cross-sectional study. Methods: PA was assessed objectively for 6 days in 273 children (aged 7.1 ± 0.6 years). In total, 74 children (27%) were classified as having a migration background. PA was grouped in light and moderate-to-vigorous (MVPA) intensities. Body mass index (BMI) percentiles (BMIPCT) were determined. Results: Children without a migration background spent more time in MVPA compared with children with a migration background (138.2 ± 62.6 vs 121.7 ± 54.9 min, respectively; P  < 0.01). On weekends, time in MVPA decreased significantly for all children (112.3 ± 66.0 min, P  < 0.01), especially for children with a migration background (97.7 ± 56.7 min, P  < 0.01). Children with a migration background displayed significantly higher BMIPCT than children without a migration background (55.7 ± 29.6 vs 44.3 ± 26.8, respectively; P  < 0.01) and were significantly more often overweight and/or obese (13.5% vs 8.5%, respectively; P  < 0.02). Conclusions: Children with a migration background are less physically active and more often overweight, resulting in higher risks of developing secondary diseases. The results of this study should be considered when designing interventions to increase PA in children with a migration background. Trial registration: German Clinical Trials Register (DRKS), DRKS-ID: DRKS00000494; Highlights: Children with a migration background spent significantly less time in moderate-to-vigorous physical activity (MVPA). On weekends, children spent significantly more time being sedentary. Children with a migration background reached the MVPA guidelines more often. Children with a migration background displayed significantly higher body mass index percentiles.